Long-Term Expansion of Porcine Intestinal Organoids Serves as an in vitro Model for Swine Enteric Coronavirus Infection - Zhang, Min; Lv, Lilei; Cai, Hongming; Li, Yanhua; Gao, Fei; Yu, Lingxue; Jiang, Yifeng; Tong, Wu; Li, Liwei; Li, Guoxin; Tong, Guangzhi; Liu, Changlong (Frontiers in Microbiology, 2022)
A reliable and reproducible model in vitro for swine enteric coronaviruses infection would be intestinal models that support virus replication and can be long-term cultured and manipulated experimentally. Here, we designed a robust long-term culture system for porcine intestinal organoids from the intestinal crypt or single LGR5+ stem cells by combining previously defined insights into the growth requirements of the intestinal epithelium of humans. We showed that long-term cultured swine intestinal organoids were expanded in vitro for more than six months and maintained the potential to differentiate into different types of cells. These organoids were successfully infected with porcine enteric coronavirus, including porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV), and were capable of supporting virus replication and progeny release. RNA-seq analysis showed robust induction of transcripts associated with antiviral signaling in response to enteric coronavirus infection, including hundreds of interferon-stimulated genes and cytokines. Moreover, gene set enrichment analysis indicated that PEDV infection could suppress the immune response in organoids. This 3D intestinal organoid model offers a long-term, renewable resource for investigating porcine intestinal infections with various pathogens.